If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 + -10x + 12x = 17 Combine like terms: -10x + 12x = 2x -27 + 2x = 17 Solving -27 + 2x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 2x = 17 + 27 Combine like terms: -27 + 27 = 0 0 + 2x = 17 + 27 2x = 17 + 27 Combine like terms: 17 + 27 = 44 2x = 44 Divide each side by '2'. x = 22 Simplifying x = 22
| -10.1+2.1(-1.4+4.1h)= | | 20b^2-13bx-15x^2=0 | | 6x-18=3x-18 | | 93+w=117 | | -3x-3x-3x-3x-3= | | P=8-ln(q+2) | | 60+3d=0+8d | | x/15+4=3 | | 5x=a-8 | | x^2+6x+8x=0 | | 2y-14=10-2y | | 2v^2-9v-3=2 | | xy-5y+7x-35=0 | | 12b^2+56x-25x^2=0 | | 8.1(-4.7q+-7.9)+-2.6q= | | 10x-11=7x+14 | | xy-5y+7y-35=0 | | -5(v+3)=33+7v | | 2+5x-17=12x-11-7x | | 20a^2+19a+3=0 | | (0.8a-0.3)(0.13a+1)=0 | | 8(x+4)=8(x+9) | | 0=10x-(7+10x) | | (4x+4y)=80 | | 3x-(4x+36)=20 | | 3x+2(12)=18 | | (b+2)(b-2)=(b+8)(b-3) | | n/5-3=-8 | | 50=9x+7+2 | | 7-(3x+1)+8(2x-3)=4(3x-1)-7(x-4) | | 24x^2+14x-5=0 | | (3c+7)(c+6)=0 |